2004
DOI: 10.1038/sj.bjc.6601654
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of pain and quality of life during the year before death in men with prostate cancer

Abstract: In order to explore how health-related quality of life changes towards the end of life, a questionnaire including the EuroQOl form and the Brief Pain Inventory form was sent to all men with prostate cancer in the county of Ö stergö tland, Sweden, in September 1999. Responders who had died prior to 1 January 2001 were later identified retrospectively. Of the 1442 men who received the questionnaire, 1243 responded (86.2%). In the group of responders, 167 had died within the study period, 66 of prostate cancer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…The threshold increases with respect to , reflecting the decreased benefits of screening represented by a higher disutility of treatment. Figure 5(i) is the one-way sensitivity analysis for the disutility of metastasis, γ, with lower bound γ = 0.15 from Krahn et al (2003) and upper bound γ = 0.46 from Sandblom et al (2004). As illustrated in Figure 5(i), When γ was decreased to 0.15 the optimal biopsy threshold increased, implying patients should be subjected to less aggressive prostate cancer screening, and vice versa when γ was perturbed to 0.46.…”
Section: Computational Experiments and Sensitivity Analysismentioning
confidence: 99%
“…The threshold increases with respect to , reflecting the decreased benefits of screening represented by a higher disutility of treatment. Figure 5(i) is the one-way sensitivity analysis for the disutility of metastasis, γ, with lower bound γ = 0.15 from Krahn et al (2003) and upper bound γ = 0.46 from Sandblom et al (2004). As illustrated in Figure 5(i), When γ was decreased to 0.15 the optimal biopsy threshold increased, implying patients should be subjected to less aggressive prostate cancer screening, and vice versa when γ was perturbed to 0.46.…”
Section: Computational Experiments and Sensitivity Analysismentioning
confidence: 99%
“…In addition, as part of the review of utility estimates for HRPC patients, only a single study was identified reporting societal valuations using a standardised and validated generic instrument for the main utility estimates. 77 Although this study was considered the most appropriate source of utility for the purposes of our main analysis, the review demonstrated considerable variation within the other estimates identified. Although some of this variation can be attributed to the different methods of valuing particular health states (e.g.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…77 They reported that the QoL of the population of men with prostate cancer decreases during the final year of life, with a range of (mean) utility values from 0.58 to 0.46 covering different periods during the last 12 months of a patient's life. The average value reported across the final year was reported to be 0.538 (95% CI: -0.077 to 0.077).…”
Section: Figure 5 Spectrum Of Hrqol's Utility Values For Prostate Cancermentioning
confidence: 99%
“…Utility during docetaxel therapy was based on a study which measured EuroQol-5D (EQ-5D) in the year before death from prostate cancer. [15] The utility post-docetaxel therapy was set equivalent to the utility prior to docetaxel for patients requiring pain relief with opioids.…”
Section: Cost-effectiveness Evidencementioning
confidence: 99%